RESEARCH METHODS IN MENTAL RETARDATION PSYCHOLOGY - Vera Tejeiro, Ana (Anales de Psicología / Annals of Psychology)
This work deals with different methods used in the research into mental retardation according to the specific problem they wish to study: organic etiology, intelligence, social adaptation and personality. Together with the epidemiological, experimental, cuasi experimental and correlational methods, qualitative methods are studied which have recently been re-introducted in the research of the social sciences.